2015
DOI: 10.1186/1471-2164-16-s7-s2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signatures of a disease in potential biomarker space: Getting the signatures consensus and identification of novel biomarkers

Abstract: BackgroundThe lack of consensus among reported gene signature subsets (GSSs) in multi-gene biomarker discovery studies is often a concern for researchers and clinicians. Subsequently, it discourages larger scale prospective studies, prevents the translation of such knowledge into a practical clinical setting and ultimately hinders the progress of the field of biomarker-based disease classification, prognosis and prediction.MethodsWe define all "gene identificators" (gIDs) as constituents of the entire potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Despite differences in study design, goals, samples, and patients, these three miRNAs were found within the MSC classifier. This finding contrasts with other studies that observed low degrees of overlap between signatures [34]. Our 3-miRNA signature (miR-16-5p, miR-92a-3p, and miR-451a) may be robust for lung cancer early detection, since it was distinctly found in lung cancer patients only, which were mostly of Stage I (62%; 48/78).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite differences in study design, goals, samples, and patients, these three miRNAs were found within the MSC classifier. This finding contrasts with other studies that observed low degrees of overlap between signatures [34]. Our 3-miRNA signature (miR-16-5p, miR-92a-3p, and miR-451a) may be robust for lung cancer early detection, since it was distinctly found in lung cancer patients only, which were mostly of Stage I (62%; 48/78).…”
Section: Discussioncontrasting
confidence: 99%
“…Genes MAP2K3 and MAPKAPK3 are found to play a role in BMI ( Bian et al 2013 , Shao et al 2022 ). Other genes in MAPK signaling that are not significant according to the gene scores ( RPS6KA4, DUSP4, MAPKAPK5 ) have also been associated with obesity ( Ow and Kuznetsov 2015 ). EEF2K is also predicted to be a novel target for obesity ( Joshi et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…To test the novelty of genes in 22g-TAG, we compared our 22g-TAG with reference lists of 72 BC gene signatures previously published in other studies and collated by our group [ 36 , 37 ] (including 2 grading signatures from previous studies [ 18 , 20 ]). Only one gene ( CAPN8 ) can be considered a novel IDC-associated gene.…”
Section: Resultsmentioning
confidence: 99%